Analysis Of The Marketing Strategy Of Tanjung Kodok Beach Resort In Increasing Foreign Tourist Visits In 2022-2023 - Amelia Fatimatuzzahra (Sean Institute, 2024)
Tanjung Kodok Beach Resort is one of the accommodation type tourism businesses in Lamongan which was built on the beach in Paciran District. Tanjung Kodok Beach Resort is also the only accommodation type tourism business in East Java which was built directly facing the sea which leads to views of North Lamongan Beach. Although the northern area of Lamongan has many similar accommodations such as guesthouses and homestays. However, the majority of foreign tourists visiting Lamongan in 2023 prefer to stay at Tanjung Kodok Beach Resort. This research will try to examine the marketing strategies used by Tanjung Kodok Beach Resort to maintain its existence in this situation. This research uses a qualitative-descriptive research method with data collection techniques from interview and documentation studies. The results of this research found that Tanjung Kodok Beach Resort has several marketing strategies to increase foreign tourist visits, which are; (1) Place, Tanjung Kodok Beach Resort was built in a strategic area, namely a coastal area close to various tourist destinations and companies operating on an international scale; (2) Product, Tanjung Kodok Beach Resort provides various room facilities, sports, banquet facilities and various places to relax so that it can be used by people in the world at any age, both children and adults for the purpose of business, holiday alone, with friends or family; (3) Price, Tanjung Kodok Beach Resort sets prices that are representative of the quality that offered, starting from Rp. 645,000 to Rp. 3,999,000; and (4) Promotion, Tanjung Kodok Beach Resort uses 3 forms of promotion, which are sales promotion through discount vouchers, mass selling through Instagram and websites, and personal selling through table-top activities in Malaysia.